Caco-2 Permeability Studies and In Vitro hERG Liability Assessment of Tryptanthrin and Indolinone - Jähne, Evelyn A.; Eigenmann, Daniela E.; Moradi-Afrapoli, Fahimeh; Verjee, Sheela; Butterweck, Veronika; Hebeisen, Simon; Hettich, Timm; Schlotterbeck, Götz; Smieško, Martin; Hamburger, Matthias; Oufir, Mouhssin (Planta Medica, 2016)
Tryptanthrin and (E,Z)-3-(4-hydroxy-3,5-dimethoxybenzylidene)indolinone (indolinone) were recently isolated from Isatis tinctoria as potent anti-inflammatory and antiallergic alkaloids, and shown to inhibit COX-2, 5-LOX catalyzed leukotriene synthesis, and mast cell degranulation at low µM to nM concentrations. To assess their suitability for oral administration, we screened the compounds in an in vitro intestinal permeability assay using human colonic adenocarcinoma cells. For exact quantification of the compounds, validated UPLC-MS/MS methods were used. Tryptanthrin displayed high permeability (apparent permeability coefficient > 32.0 × 10−6 cm/s) across the cell monolayer. The efflux ratio below 2 (< 1.12) and unchanged apparent permeability coefficient values in the presence of the P-glycoprotein inhibitor verapamil (50 µM) indicated that tryptanthrin was not involved in P-glycoprotein interactions. For indolinone, a low recovery was found in the human colon adenocarcinoma cell assay. High-resolution mass spectrometry pointed to extensive phase II metabolism of indolinone (sulfation and glucuronidation). Possible cardiotoxic liability of the compounds was assessed in vitro by measurement of an inhibitory effect on human ether-a-go-go-related gene tail currents in stably transfected HEK 293 cells using the patch clamp technique. Low human ether-a-go-go-related gene inhibition was found for tryptanthrin (IC50 > 10 µM) and indolinone (IC50 of 24.96 µM). The analysis of compounds using various in silico methods confirmed favorable pharmacokinetic properties, as well as a slight inhibition of the human ether-a-go-go-related gene potassium channel at micromolar concentrations.
Keywords: Caco-2; metabolism; U(H)PLC-MS/MS; validation; HR-MS; hERG; Isatis tinctoria